(untitled) (Archives of Clinical and Medical Case Reports, 2025)
Introduction: Cerevisiae is a probiotic micro-organism whose use in food is known to have beneficial effects on digestion and several gastrointestinal disorders. However, while probiotics are commonly used, they can be dangerous for certain people, especially those with immuno-compromised systems, who can develop fungemia and subsequently die. This case report describes a case of fungemia in a newborn baby that was not diet-related (lactation). Case presentation: We present for the first time a case of S. cerevisiae fungemia isolated in a blood culture from a two-hours-old newborn who presented with vomiting and a disturbance of vital and biological signs immediately after taking formula milk powder containing no probiotics (Nestlé NAN 1). Despite this less severe clinical picture, the symptoms disappeared rapidly after three days, without the need to administer antifungal agents. The isolated S. cerevisiae was probably wild type, as it was sensitive to the antifungal agents tested, and the symptoms resolved after five days, with the baby being discharged from hospital on day 7. Conclusion: The risk of S. cerevisiae fungemia remains present in all newborns with signs of infection, whether they are on an S. cerevisiaebased diet. Transmission of S. cerevisiae that is not diet-related, remains a real challenge, and several studies need to be carried out to elucidate its involvement in fungemia.